Wing shape differences along a migration route of the long-distance migrant Globe Skimmer Dragonfly Pantala flavescens - Johansson, Frank; Kollberg Hedström, Tobias; Anderson, R. Charles; Divakaran, Prathapan K.; Kakkassery, Francy K. (Journal of tropical ecology, 2022)
Animals which migrate by flying should be subject to selection for optimal wing characteristics that maximize energy efficiency during migration. We investigated wing shape and wing area variation in the Globe Skimmer Dragonfly Pantala flavescens , which has the longest known migration of any insect. Wing shape and wing area differences between individuals in southern Peninsular India, and migrating individuals at a stop-over site on the Maldives, were compared. Results suggest that individuals which successfully reached the Maldives, on their way from India to Africa, had a broader wing base and an overall more slender wing shape than individuals in southern India. Contrary to our expectations, wing area did not differ significantly in most of our comparisons between southern India and the Maldives, suggesting that wing shape is more important than wing area for successful migration in P. flavescens . The results provide indirect evidence of natural selection on wing shape in a migrating dragonfly.